Merkel Cell Carcinoma with Distant Metastasis to the Clivus Causing Symptoms Mimicking Tolosa–Hunt Syndrome: A Case Report and Literature Review - Ho, Kwo Wei David; Drew, Peter A.; Chuquilin, Miguel (Frontiers in Neurology, 2017)
Merkel cell carcinoma (MCC) is an uncommon but highly malignant neuroendocrine tumor of the skin. MCC can metastasize, but involvement of the central nervous system is rare. Here, we report a case of rapidly progressing metastatic MCC to the clivus and bilateral cavernous sinus in an immunocompromised patient. This case is unique in that it is the first case report showing MCC metastasis to the clivus from a distant site. It also demonstrates that a MCC metastasis can masquerade with symptoms of Tolosa–Hunt syndrome. A literature review on MCC with CNS metastasis is presented.